(untitled) (Faridpur Medical College Journal, 2018)
More than one half of intracranial lipomas are associated with varying degrees of brain malformations. Associated anomalies include agenesis of surrounding tissues, frontal bone defects or facial dysplasia and cerebral vascular defects. Agenesis of corpus callosum can be associated with a midline lipoma with or without calcification of its periphery. This developmental abnormality has an embryological basis. We observed this in 1 case, and as this is uncommon, are reporting this. Faridpur Med. Coll. J. Jan 2018;13(1): 47-49